Preparation, Characterization and Study of the Photodecolorization of Mixed-Ligand Binuclear Co(II) Complex of Schiff Base by ZnO - Suhad Kareem Abass; Jassim Abbas Al-Hilfi; Sawsan Khudhair Abbas; Luma Majeed Ahmed (Universitas Gadjah Mada, 2020)
In this work, a new mixed-ligand binuclear Co(II) complex of Schiff base was prepared. Moreover, the characterization of this prepared complex was performed by measurement of melting points, UV-Vis spectra, FT-IR spectra, and magnetic susceptibility measurements, and later compared with metal and ligand solutions. It has been discovered that the Schiff bases with Co(II) ion forms a binuclear complex with a stoichiometry of molar ratio 1:2 from “metal:ligand”. The photodecolorization of this complex was done under UV light for ZnO's suspension solution. The results of this photodecolorization showed that the greatest efficiency was obtained with the use of ZnO dose of 300 mg/100 mL and at an initial pH of 7. The decolorization activation energy for this complex is a small value of 11.289 kJ mol–1. Additionally, the thermodynamic study for this reaction is non-spontaneous, endothermic and less random.